A new approach to protecting ecosystems: The Te Awa Tupua (Whanganui River Claims Settlement) Act 2017. (December 2017) - Rodgers, Christopher
The Te Awa Tupua (Whanganui River Claims Settlement) Act 2017 settled the longest-running litigation over Maori land claims in New Zealand history. The Whanganui river is New Zealand's longest navigable river, stretching from Mount Tongariro in the North Island to the Tasman Sea. The settlement, and the 2017 Act which implements it, confers legal personality on the river system, giving it a unique legal status that recognises not only the need to protect the ecosystem it represents, but also to provide a legal forum in which to implement Maori cultural and spiritual attitudes to the relationship of land and people. It can be argued this marks a new and innovative approach to protecting the environment, focusing at the ecosystem level and incorporating spiritual values in a manner unknown in environmental law in most Western legal systems. This is not, however, the first time that an approach based on principles found in the 2017 Act has been used in a New Zealand context. This article will consider the 2017 Act and its principal objectives, and set the legislation within the very distinctive context of the legal culture within which environmental law in New Zealand sits. It highlights differences of approach from those adopted in English law to similar problems of ecosystem management, and concludes by considering whether (and what) lessons can be drawn from this innovative approach for the wider environmental governance of the natural environment.